Political Communication Strategy of Joko Pramono in the 2024 Elections in Karanganyar District IV - Hasanah, Thalisa Nur; Sanjaya, Andika (Universitas Syiah Kuala, 2025)
his study aims to analyze the political communication strategies implemented by Joko Pramono as a member of the Regional Representative Council in the 2024 elections in Electoral District IV Karanganyar. Specifically, this study focuses on social media, particularly Instagram, using the account @masjokpram. This study employs the impression management Theory. According to Jones and Pittman, five strategies can be applied: Ingratiation, Intimidation, Self-Promotion, Exemplification, and Supplication. This study employs a descriptive approach, utilizing data collection techniques that include in-depth interviews, observation of social media posts, and other forms of documentation. The primary focus of this study is how Joko Pramono builds his political image and establishes closeness with the public through social media, particularly Instagram. The data analysis technique used is content analysis. The object of this study is the Instagram account @masjokpram during the 2024 election. Triangulation was conducted to achieve an objective and in-depth understanding. The results of the survey demonstrate that Joko Pramono utilizes Instagram as a political communication strategy.